ILE655VAL Genotyping Study of HER2 - Positive Breast Cancer of Patients from Padang - Indonesia With High Resolution Melting Technique - Dwi Wulandari; Azamris Azamris; Isna Nurhayati; M Ali Warisman; Bugi Ratno Budiarto; Desriani Desriani (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2017)
Transtuzumab has proven to be a great improvement in the treatment of HER2 + of breast cancer patients, but it is associated with relevant adverse cardiac events and with significantly elevated cost of treatment. One of the risk factors for cardiotoxicity due to transtuzumab is the I655V HER2 polymorphism (GTC> ATC mutation) in which the allele mutant (Ile val or val / val) has a higher risk than the wild type (Ile/Ile). The detection of specific alleles is very important for therapeutic decision-making. In this study, our group have developed a HRM with EvaGreen dye method to discriminate specific allele of I655V HER2 (wild type, heterozygote mutant or homozygote mutant) in 66 frozen section samples of HER2+ of breast cancer patients. Our group reported the wild type is the most prevalent allele (77,27%), whereas heterozygous mutation is significantly present in this research (21,21%) and only 1,52% of sample detected as minor allele. It showed that only one sample detected as a minor allele (val/val) and may have relatively low abundance in the population. This method has been compared with sanger sequencing and giving 100% of validity.